The relationship between fluid biomarkers and clinical outcomes in sports-related concussions: a systematic review. (18th September 2020) - Meyer, Jessica; Bartolomei, Christopher; Sauer, Adam; Sajatovic, Martha; Bailey, Christopher M
ABSTRACT: Objectives: The literature on fluid biomarkers for concussion has primarily focused on comparing athletes with and without a diagnosis of concussion and on examining the relationship between fluid biomarkers and exposure to head trauma. This systematic literature review aims to examine the strength of evidence for fluid biomarkers to be associated with clinically relevant outcomes in sports-related concussion. Methods: A systematic literature review was conducted using EmBASE, PubMed, and CINAHL. English-language articles that included athletes participating in organized sports and reported the relationship between at least one fluid biomarker and at least one clinical outcome measure, or provided data that could be used to analyze this relationship, were included. Results: Studies of the relationship between fluid biomarkers and clinical outcomes of concussion have yielded small or variable effects. There were significant inconsistencies in methodology including duration of time post-injury of biomarker collection, use of control groups, the number of time points post-injury that biomarkers were collected, and what clinical outcomes were utilized. Conclusion: There is currently insufficient evidence to support a relationship between any of the included fluid biomarkers and clinical outcome measures of concussion. Future research including clinical outcome measures and using standardized study design and methodology is necessary.